The Impact of Learning Style and Learning Motivation on Students’ Science Learning Outcomes - Suciani, Ni Komang; Sudarma , I Komang; Bayu, Gede Wira (Universitas Pendidikan Ganesha, 2022)
Elementary school students tend to have different learning styles. Teachers can still not adjust the learning process to the student’s learning styles and have not maximally provided good learning motivation, which impacts students' low science learning outcomes. This study analyzes the significant relationship between learning styles and science learning outcomes. This research is classified into the type of correlation research, with the research population being 196 students. The study was conducted using a proportional sampling technique, with a final sample size of 149 respondents. Data collection in the study was conducted using a non-test method, with the research instrument in the form of a questionnaire on the level of learning motivation and learning style. The research instrument's validity was tested through expert tests (judges). Data analysis used descriptive statistical analysis and inferential statistical analysis. The descriptive statistical analysis method processes descriptive, while inferential statistics data processing applies inferential statistical formulas. The first hypothesis test results show 0.609 > 0.159, so hypothesis 1 is accepted. There is a correlation between learning styles and learning outcomes in science. The results of hypothesis 2 are 0.625 > 0.159, so there is a correlation between learning motivation to students' science learning outcomes. The results of hypothesis 3 are 0.625 > 0.159, so there is a correlation between learning styles and learning motivation on science learning outcomes. Based on these results, it can be concluded that learning styles and students' motivation while studying significantly influence student learning outcomes.